Climate justice between Nations: The Global North and South (A comparative study) - Mohammed, Dr. Mohammed Hameed (Tikrit Journal For Political Science, 2024)
The issue of climate change is one of the biggest challenges facing the world in the current century, as this changing environmental circumstance leads to fundamental impacts on ecosystems, which in turn is clearly reflected in the life of living organisms on planet Earth. With the increased consumption of natural resources and increasing human needs, many feel Given the seriousness of the environmental transformation facing us, the lack of a clear direction for transitioning to a sustainable and just system, and given the transformations sweeping the planet, climate justice has become an important topic that deserves our serious attention. In this context, the concept of climate justice highlights the need for a fair distribution of responsibility and sacrifices in facing the challenges of climate change, as the need arises to provide the necessary financing, technologies and resources to the countries of the South to help them adapt to the effects of climate change and reduce its negative impacts. These circumstances make studying climate justice between countries of the North and South necessary, to understand the existing gaps and develop effective ways to achieve balance and justice in countries’ dealings with the challenges of climate change.